The role of child’s age, sex, and temperament in father involvement during the pre-school years - Santos, C. (2022)
(1) Background: The aim of the study was to explore how child’s characteristics (age, sex, and temperament) were associated with father’s involvement in child-related activities. In a sample of 410 bi-parental families with pre-school age children. (2) Methods: Dividing the sample into two age groups, OLS regression models were conducted for each dimension of father involvement with child characteristics as predicting variables. (3) Results: for the younger children (3 and 4 years) fathers were more involved in teaching/discipline and played with their more extroverted daughters. With older children (5 and 6 years), fathers were more involved in teaching/discipline and played when children were higher on negative-affectivity. An interaction was found with boys’ higher negative- affectivity, predicting fathers’ higher involvement in teaching and discipline. (4) Conclusions: Our results suggest that children’s characteristics have an impact on what fathers do, particularly in a dimension salient to pre-school years such as teaching/discipline. This can help build tailored empirical-sustained programs aiming to encourage and support fathers’ positive involvement. Keywords: father involvement; child’s age; child’s sex; child’s temperament; preschool